2020
DOI: 10.1093/brain/awaa140
|View full text |Cite
|
Sign up to set email alerts
|

Slow blood-to-brain transport underlies enduring barrier dysfunction in American football players

Abstract: Repetitive mild traumatic brain injury in American football players has garnered increasing public attention following reports of chronic traumatic encephalopathy, a progressive tauopathy. While the mechanisms underlying repetitive mild traumatic brain injury-induced neurodegeneration are unknown and antemortem diagnostic tests are not available, neuropathology studies suggest a pathogenic role for microvascular injury, specifically blood–brain barrier dysfunction. Thus, our main objective was to demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 77 publications
2
50
0
Order By: Relevance
“… 23 Magnetic resonance imaging studies have demonstrated that players exposed to repetitive head impacts over the course of a season show significant abnormalities compared to controls over the same time period and that these abnormalities are related to the extent of exposure to head impacts. 4 , 5 , 24 …”
Section: Discussionmentioning
confidence: 99%
“… 23 Magnetic resonance imaging studies have demonstrated that players exposed to repetitive head impacts over the course of a season show significant abnormalities compared to controls over the same time period and that these abnormalities are related to the extent of exposure to head impacts. 4 , 5 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether these structural white matter findings reflect neurodegenerative changes, especially in younger, asymptomatic participants. However, several studies document cerebrovascular pathophysiology associated with repetitive head trauma, including altered cerebral perfusion dynamics [ 64 , 94 97 ] and blood–brain-barrier dysfunction [ 98 , 99 ], which may produce white matter signal abnormalities on MRI. In CTE cases, more severe white matter rarefaction is associated with greater exposure to repetitive head trauma, severity of neurofibrillary tangle deposition, and likelihood of developing dementia [ 32 ].…”
Section: Structural Mrimentioning
confidence: 99%
“…Although the present study has a small number of participants, we think that it can play a role as an introductory study that can help determine the pathophysiology of AD or plan a drug treatment strategy in the future. Secondly, our DCE imaging acquisition time was only 10 min, which is relatively short compared to recent recommendations [ 26 , 27 ]. Slow subtle BBB leak could be better visualized using a modified DCE protocol with a longer acquisition time (>16 min) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our DCE imaging acquisition time was only 10 min, which is relatively short compared to recent recommendations [ 26 , 27 ]. Slow subtle BBB leak could be better visualized using a modified DCE protocol with a longer acquisition time (>16 min) [ 26 ]. However, in terms of clinical practice, 10 min appears to be the maximum acquisition time which limits motion in elderly patients.…”
Section: Discussionmentioning
confidence: 99%